Medicinal plants for postpartum care among the Acehnese, Indonesia - ZUMAIDAR ZUMAIDAR; SAUDAH SAUDAH; ESSY HARNELLY (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Zumaidar, Saudah, Harnelly E. 2026. Medicinal plants for postpartum care among the Acehnese, Indonesia. Biodiversitas 27 (7): d270705. https://doi.org/10.13057/biodiv/d270705. Traditional plant-based postpartum therapies remain widely practiced in Aceh Province, Indonesia, but comprehensive quantitative documentation of the medicinal plants involved and their regional variation is still limited. This study aimed to analyze the diversity, distribution, and cultural salience of medicinal plants used in postpartum care among the Acehnese Ethnic Group. Ethnobotanical data were collected through semi-structured interviews, participatory observation, and field surveys involving 1,306 informants across one city and five districts: Banda Aceh, Pidie Jaya, Pidie, Bireuen, Aceh Jaya, and Aceh Besar. Data were analyzed using descriptive ethnobotanical statistics, Relative Frequency of Citation (RFC), and heatmap-based spatial analysis. A total of 73 species representing 38 families were documented. Zingiberaceae was the most represented family. RFC analysis identified Curcuma longa, Carica papaya, Lawsonia inermis, Nigella sativa, and Zingiber officinale as the most culturally prominent taxa. Heatmap analysis revealed pronounced spatial heterogeneity, with Aceh Besar and Bireuen exhibiting the highest species richness. Leaves constituted the most frequently utilized plant part, while grinding and pounding were the predominant preparation methods. Oral administration was the principal mode of use. Seven major postpartum treatments were documented. These findings demonstrate the continued importance of plant-based therapies in maternal healthcare and provide a valuable baseline for biodiversity conservation and biocultural research.